A cross-disciplinary approach to product development and design through quality function deployment, target costing and value engineering. (1st January 2012) - Sharma, Jitendra
Increased competition, spiralling costs and vocal customers have made it imperative that every organisation should upgrade its processes constantly to stay ahead of the competition. Product design and development (PDD) is a techno-economic process, hence there is always a trade-off between design goals and cost constraints. Quality function deployment (QFD) is becoming a widely used customer-oriented approach and tool in product design. Target costing (TC) is a strategic tool for planning that takes a holistic view of products and their sub-assemblies, and identifies the opportunities for cost reduction and product improvement. Value engineering (VE) is essentially a process which uses function-cost analysis to reduce cost. This paper attempts to merge these diverse tools of customer-orientation, financial consideration and value creation, thus integrating TC and VE into QFD framework. The suggested methodologies aim at facilitating cross-functional PDD, integrating both organisational and functional aspects of the development process so as to maximise value creation. A case study has been discussed and issues of implementation of this cross-disciplinary approach from the perspective of an entrepreneur by selecting a consumer product are highlighted.